A hybrid FVM-FEM simulator for coupled multiphysics: Application to field-scale CO2-ECBM - Yulong Liu; Yanjun Zhang; Guanhong Feng; Yuxiang Cheng; Xuefeng Gao; Tianfu Xu (Computers and Geotechnics, 2026)

Size-resolved airborne particle control in a dental operatory: field comparison of window opening, portable air purifier, and UV air disinfection - Chen Chen; Di Zhang; Xiaoyi Xiao; Chuanhao Wang; Ruixin Nie; Xiaojing Lin; Mengmeng Cao; Meiqiu Hong; Yanjun Su; Bin Zhao; Shanshan Shi; Mingyao Yao; et al. (Building and Environment, 2026)

Molecular basis for the divergence in aroma profiles between traditional and modern industrial soy sauce by quantitative metabolomics and sensory reconstitution - Xinyu Zhang; Li Li; Mouming Zhao; Yanjun Li; Yunzi Feng (Food Chemistry, 2026)

Ultrafast electrothermal stabilization of heavy metals in municipal solid waste incineration fly ash by flash Joule heating - Yingchao Liu; Wenjing Lu; Liwen Zhang; Yanjun Liu; Erkang Feng; Zhenyu Ren; Teng Wang; Mingyue Xu; Dongbei Yue; Bing Deng (Journal of Hazardous Materials, 2026)

Chronic heat exposure induces brain atrophy in mice: Molecular signatures and AI-driven intervention strategy - Wenxin Xiang; Bo Yin; Qi Huang; Shisu Li; Miaohui Ding; Guoqing Feng; Ruoran Li; Dizhi Wang; Leizi Min; Xingyuan Hu; Limei Ke; Linfeng Liu; et al. (Journal of Environmental Sciences, 2026)

Egg yolk phospholipid peptides as dual-functional nanocarriers for curcumin: Enhanced hypolipidemic effects and mechanism - Ruyi Zhang; Wenhui Feng; Lili Jiang; Cuihua Chang; Luping Gu; Yujie Su; Yanjun Yang; Yi Wang; Junhua Li (Food Research International, 2026)

Stimulating sulfur metabolism by overexpression of Sulfide:quinone reductase in Acidithiobacillus caldus coupled with low pH-high S0 integrated strategy in chalcocite bioleaching - Ruian Ji; Mingwei Wang; Xingyu Huo; Yiwen Zhu; Zhidong Guo; Yingming Wang; Jia Wang; Hailin Yang; Yanjun Tong; Shoushuai Feng (Bioresource Technology, 2026)

Ephedplics E-I: three lignans and two benzofuran-type compounds from the roots of Ephedra sinica Stapf and their neuroprotective activity - Yunlong Dou; Bowen Zhang; Meng Li; Xiaolan Wang; Shuyan Liu; Yanjun Sun; Xiaoke Zheng; Weisheng Feng (Journal of Natural Medicines, 2026)

Failure mechanism and damage assessment of talus slopes with varied gradation under seismic loading - Xing Wei; Shitao Cheng; Rui Chen; Xinle Zhai; Jun Feng; Zijian Wang; Yanjun Li; Le Cheng (Landslides, 2026)

Integrating very-high-resolution imagery, Sentinel-2 time-series data, and machine learning to map shrub fractional abundance across arid and semi-arid ecosystems in China - Zhonghua Liu; Yuhao Feng; Xin Cao; Josep Peñuelas; Adrià Descals; Daryl Yang; Ka Kin Cheung; Shuwen Liu; Ziyu Lin; Xiaoqiang Liu; Xiaoyong Wu; Han Ma; et al. (Remote Sensing of Environment, 2026)

Enzyme-detonated CRET nanocascade ignites endogenous chemiluminescence to empower self-sufficient photodynamic therapy and tumor-specific imaging - JiaXin Zhu; YanJun He; XiaoQian Wu; KangDi Teng; YiTeng Long; Yuan Zhang; Hui Sun; WenYuan Liu; Feng Feng; Wei Qu (Chemical Engineering Journal, 2026)

CSSL-based GWAS identifies SNPs and candidate genes associated with Verticillium wilt resistance in cotton - Youzhong Li; Xiaohui Jiang; Hongyu Cao; Xinyu Zhang; Zhongxu Lin; Qian-Hao Zhu; Yanjun Li; Fei Xue; Shuaishuai Cheng; Feng Liu; Jie Sun (Theoretical and Applied Genetics, 2026)

Microwave assisted alkali activated porous carbon from phenolic resin waste for high capacity methylene blue removal - Yanjun Yin; Mengjie Bai; Wenxu Wang; Xiaotian Zhao; Weide Yuan; Yongwei Li; Yuying Yan; Yujie Feng; Wenjie Zhu; Xinyu Wang; Zhihao Fang; Wei Zhang (Environmental Geochemistry and Health, 2026)

Study on the treatment of complex water hardness using electrocoagulation coupled with electrodeposition - Yanlong Sun; Hangyang Feng; Qianwei Liang; Meijuan Bian; Weifeng Kong; Xingzhi Mao; Qianwen Wang; Chengzhi Zhou; Yanjun Xin; Liguo Shen (Process Safety and Environmental Protection, 2026)

Developing fed-batch strategies to improve high-solid enzymatic hydrolysis of steam-exploded apple pomace - Ruijin Yang; Huanqi Shu; Nuo Xu; Wenhui Zheng; Wei Zhao; Shoushuai Feng; Yanjun Tong (Food Bioscience, 2026)

Egg yolk phospholipid peptide-dihydromyricetin nano-composites: Temperature-driven assembly and evaluation of stability and pharmacokinetics - Yingxin Wei; Jinping Zhang; Wenhui Feng; Cuihua Chang; Luping Gu; Yujie Su; Yanjun Yang; Junhua Li (Food Bioscience, 2025)

In situ probing and microstructural evolution mechanisms of hydrogen-derived manganosite (MnO) during oxidative cooling - Wu Zijian; Yuan Shuai; Zhu Feng; Gao Peng; Li Yanjun; He Jiahao (Minerals Engineering, 2025)

Multi-component heterogeneous interface engineering and magnetic domain evolution for broadband electromagnetic wave attenuation - Yuhui Peng; Jiarong Liu; Zhaobo Feng; Jinbin Peng; Yangxiao Guo; Yue Zhang; Yanjun Fu; Chongbo Liu; Lianwen Deng (Chemical Engineering Journal, 2025)

Fe/Fe3O4/FexN@N-doped porous carbon aerogels with superior electromagnetic attenuation performance and multifunctional applications - Yumei Ren; Zhen Qin; Tong Xi; Shuai Yang; Ziran Du; Desheng Feng; Zhongyi Bai; Yanjun Zheng; Xiaoqin Guo; Biao Zhao (Chemical Engineering Journal, 2025)

Enhanced denitrification and fouling control in hydrogen-based membrane biofilm reactor using novel flat membrane module - Mingyi Lu; Quan Feng; Fan Qin; Yanjun Wu; Haoran Duan; Shanfei Fu; Rongbo Guo (Bioresource Technology, 2025)

Genome and transcriptome analysis provide insights into the genetics and breeding of Salix suchowensis growth traits - Wei Liu; Shaobo Gu; Mingjia Zhu; Yu Han; Xiaogang Dai; Huaitong Wu; Tongming Yin; Linjie Guo; Landi Feng; Yanjun Zan; Jianquan Liu (New Forests, 2025)

The use of predictive, preventive, and personalized medical approaches to optimize hypertension management - Ousman Bajinka; Lamarana Jallow; Yanjun Zhang; Xiaoxia Feng; Xianquan Zhan; Na Li (EPMA Journal, 2025)

Metabolite-derived spectral modelling can differentiate heat and drought stress under hot-dry environments - Wanlu Zhong; K.H. Cheng; Laiyin Zhou; Jiaoping Zhang; Fan Zhang; Guoyang Feng; Xinyu Zhang; Qin Ma; Yanjun Su; Shichao Jin; Hon-Ming Lam; Jin Wu (Remote Sensing of Environment, 2025)

Transcriptional regulatory factor EpsR mediates adaptation mechanism of extremophile Acidithiobacillus caldus to copper stress environment and performance in bioleaching of low-grade copper ore by enhancing “contact” mechanism - Hongguang Xie; Xingyu Huo; Xiuwen Wang; Zhidong Guo; Yang Yuan; Hailin Yang; Yanjun Tong; Shoushuai Feng (Journal of Hazardous Materials, 2025)

STANet-TLA: leveraging deep learning and prior knowledge for large-scale soybean breeding plot segmentation and high-yielding variety screening from UAV time-series data - Shaochen Li; Yinmeng Song; Ke Wang; Yiqiang Liu; Junhong Xian; Hongshan Wu; Xintong Zhang; Yanjun Su; Jin Wu; Qinghua Guo; Shan Xu; Dong Jiang; et al. (ISPRS Journal of Photogrammetry and Remote Sensing, 2025)

MOF-based hypocrellin composite nanomaterials as advanced plant-derived photosensitizers for multimodal therapy - Ying'’ao Wu; Yanjun Guo; Kaijie Feng; Miao Li; Hongxue Li; Jiasheng Wu; Pengfei Wang; Rungong Yang; Xiao He; Xiong Yin; Min Li (Chemical Engineering Journal, 2025)

Unlocking the potential of cotton-derived carbon aerogel for uranium extraction from real radioactive wastewater: A path to amidoxime and polyguanidine modification - Yang Wang; Yun Wang; Qi Ren; Zihao Feng; Yang Li; Yanjun Du; Xiaoyan Li; Yan Liu; Dingzhong Yuan; Tu Lan (Chemical Engineering Journal, 2025)

Reducing plant-derived ethylene enhances crop growth and soil functions under drought stress in subtropical agroecosystems - Jing Feng; Xiaocen Tian; Yanjun Liu; Xiaoqi Zhou (Plant and Soil, 2025)

Risk factors for severe lower respiratory tract infection among children under 5 years of age hospitalized with respiratory syncytial virus - Yanjun Wang; Yuanxuan Xiang; Ruohong Jin; Bin Li; Xingxing Feng; Qian Han; Xishu Deng; Yunfang Lu; Chengyan Zhang; Shufang Xiao (European Journal of Clinical Microbiology & Infectious Diseases, 2025)

Inspiring the potential of graphene oxide aerogel for uranium(VI) electrosorption: A precursor reconfiguration strategy and synergistic integration with polyethyleneimine - Qi Ren; Yun Wang; Yang Wang; Zihao Feng; Yanjun Du; Changfu Wang; Yan Liu; Dingzhong Yuan; Hao Jiang; Yang Li (Desalination, 2025)

Millennial-scale climate variability of the Asian summer monsoon over the last 690,000 years: insights from cave records - Xiaowen Niu; Jian Wang; Le Kang; Youwei Li; Haiwei Zhang; Xiyu Dong; Hanying Li; Lijuan Sha; Liang Yi; Ashish Sinha; Youfeng Ning; Xue Jia; et al. (Science Bulletin, 2025)

Dual-template molecularly imprinted magnetic covalent organic framework for selective extraction of bisphenols - Shu-hui Huo; Mengya Qin; Xiaonan Zhang; Pengxin Zhou; Junhao Liu; Xiaoqiang Yao; Zhengang Han; Zhentong Zhu; Yanjun Feng; Zhilan Wang; Xiaoquan Lu (Chemical Engineering Journal, 2025)

Impacts of street tree canopy coverage on pedestrians' dynamic thermal perception and walking willingness - Yijuan Sang; Yanjun Hu; Xiao Qin; Hai Yan; Renwu Wu; Fengtao Qian; Xinge Nan; Feng Shao; Zhiyi Bao (Sustainable Cities and Society, 2025)

Phosphorus addition diminishes the negative effect of nitrogen addition on methane sink in subtropical forest soils - Yanjun Liu; Wensheng Xiao; Jing Feng; Marcos Fernández-Martínez; Carly Stevens; Zemei Zheng; Xiaoqi Zhou (Science of The Total Environment, 2025)

A clean and convenient way to utilize naturally air-dried bamboo tubes and increase their economic value - Tiancheng Yuan; Yuan Feng; Tao Zhang; Wenkai Zhu; Yu Wang; Xinzhou Wang; Yanjun Li (Journal of Cleaner Production, 2025)

Multifunctional all-liquid microfluidic devices stabilized with molecular brush surfactants - Zhao Zhang; Weixiao Feng; Kaijuan Li; Jiaqiu Luo; Yunhui Wen; Yang Yang; Yanjun Lin; Shaowei Shi (Chemical Engineering Journal, 2025)

L1-Tree: A novel algorithm for constructing 3D tree models and estimating branch architectural traits using terrestrial laser scanning data - Yuhao Feng; Yanjun Su; Jiatong Wang; Jiabo Yan; Xiaotian Qi; Eduardo Eiji Maeda; Matheus Henrique Nunes; Xiaoxia Zhao; Xiaoqiang Liu; Xiaoyong Wu; Chen Yang; Jiamin Pan; et al. (Remote Sensing of Environment, 2024)

Enhancing acid resistance of Escherichia coli based on directed morphology evolutionary of key transcription factor bolA - Zongling Chen; Xingyu Huo; Jiali Wan; Jinming Che; Meiyi Deng; Yingnan Bao; Hailin Yang; Yanjun Tong; Shoushuai Feng (Food Bioscience, 2024)

Separation of Gold(I) from cyanide-containing wastewater by functional polymer inclusion membrane containing guanidinium ionic liquid - Guiping Zhu; Yanjun Chen; Yewei Qiu; Yuan Zhang; Feng Li; Fengzhi Jiang; Xiangjun Yang; Shixiong Wang (Chemical Engineering Journal, 2024)

Metal-ion-binding properties of glycyrrhiza polysaccharide extracted from Licorice: Structural characterization and potential application in drug delivery - Yanjun Yang; Mengli Yu; Yulin Mo; Yue Cheng; Bin Huang; Weilin Wang; Maomao Zhu; Xiaobin Jia; Liang Feng; Bing Yang (Carbohydrate Polymers, 2024)

Assessing the spatial-temporal impacts of underlying surfaces on 3D thermal environment: A field study based on UAV vertical measurements - Fengtao Qian; Yanjun Hu; Renwu Wu; Hai Yan; Dingsheng Wang; Zhoubing Xiang; Kechun Zhao; Qian Han; Feng Shao; Zhiyi Bao (Building and Environment, 2024)

Establishment of a standardized daily behavior collection and analysis system for brain disease models of rhesus and cynomolgus monkeys and its application in autism spectrum disorder - Xiaofeng Ren; Huimin Wang; Xiaoman Lv; Yi Zhou; Yingyin Fan; Yanjun Yu; Christoph W. Turck; Yuhui Chen; Longbao Lv; Yingzhou Hu; Hao Li; Wenchao Wang; et al. (Journal of Zhejiang University-SCIENCE B, 2024)
Complex brain diseases seriously endanger human health, and early diagnostic biomarkers and effective treatments are currently lacking. Due to ethical constraints on human research, establishing monkey models is crucial to address these issues. With the rapid development of technology, transgenic monkey models of a range of brain diseases, especially autism spectrum disorder (ASD), have been successfully established. However, to establish practical and effective brain disease models and subsequently apply them to disease mechanism and treatment studies, there is still a lack of a standard tool, i.e., a system for collecting and analyzing the daily behaviors of brain disease model monkeys. Therefore, with the goal of undertaking a comprehensive and quantitative study of behavioral phenotypes, we established a standard daily behavior collection and analysis system, including behavioral data collection protocols and a monkey daily behavior ethogram (MDBE) for rhesus and cynomolgus monkeys, which are the most commonly used non-human primates in model construction. Then, we used ASD as an application example after referring to the Diagnostic and Statistical Manual of Mental Disorders, Fifth Edition, Text Revision (DSM-5-TR), which is widely used in clinical disease diagnosis to obtain ASD core clinical symptoms. We then established a sub-ethogram (ASD monkey core behavior ethogram (MCBE-ASD)) specifically for quantitative assessment of the core clinical symptoms of an ASD monkey model based on MDBE. Subsequently, we demonstrated the high reproducibility of the system.

Comparative study on the effects of anionic, cationic, and nonionic polyacrylamide surface modified magnetic micro-particles (MMP) for anaerobic digestion treatment of vegetable waste water (VWW) - Fengyuan Zhang; Feng Zhao; Ying Chen; Yanjun Wu; Quan Feng; Rongbo Guo (Journal of Environmental Management, 2024)

Timescale dependent homogeneous assembly of lipid-polymer hybrid nanoparticles in laminar mixing for enhanced lung cancer treatment - ShiXin Li; Bing Yang; Liang Ye; ShuQi Hu; BenHong Li; Yanjun Yang; XiaoBin Jia; Liang Feng; ZhiWei Xiong (Chemical Engineering Journal, 2024)

Which street is hotter? Street morphology may hold clues -thermal environment mapping based on street view imagery - Yanjun Hu; Fengtao Qian; Hai Yan; Ariane Middel; Renwu Wu; Minghui Zhu; Qian Han; Kechun Zhao; Han Wang; Feng Shao; Zhiyi Bao (Building and Environment, 2024)

Responsive mechanism of Hemerocallis citrina Baroni to complex saline-alkali stress revealed by photosynthetic characteristics and antioxidant regulation - Shuo Chen; Qiuxue Zhou; Yuwei Feng; Yanjun Dong; Zixuan Zhang; Yue Wang; Wei Liu (Plant Cell Reports, 2024)

Low temperature and facile synthesis of nitrogen-doped hierarchical porous carbon derived from waste polyethylene terephthalate for efficient CO2 capture - Shaojie Zhou; Haiyang Xu; Shurong Wang; Hongyu Feng; Yanjun Hu; Shicheng Zhang (Science of The Total Environment, 2024)

Ethylene thiourea exposure induces neurobehavioral toxicity in zebrafish by disrupting axon growth and neuromuscular junctions - Jingming Wang; Zhiquan Yu; Yongfeng Wang; Yuanyao Chen; Lin Xiao; Yanjun Zong; Qiyuan Feng; Lianqi Peng; Huiping Zhang; Chunyan Liu (Journal of Environmental Sciences, 2024)

Insight into the effects of different ripeness levels on the quality and flavor chemistry of Noni fruit (Morinda citrifolia L.) - Xiaoai Chen; Chunhe Gu; Kexue Zhu; Fei Xu; Zhen Feng; Yanjun Zhang (Food Chemistry, 2024)

Enhancing column bioleaching of chalcocite by isolated iron metabolism partners Leptospirillum ferriphilum/Acidiphilium sp. coupling with systematically utilizing cellulosic waste - Xingyu Huo; Jianna Liu; Xianjing Hong; Haochen Bai; Zongling Chen; Jinming Che; Hailin Yang; Yanjun Tong; Shoushuai Feng (Bioresource Technology, 2024)

LC–MS Approach to Decipher a Light Chain Chromatographic Peak Splitting of a Monoclonal Antibody - Yanjun Liu; Zac VanAernum; Yue Zhang; Xinliu Gao; Mariana Vlad; Bo Feng; Robert Cross; Bruce Kilgore; Alice Newman; Dongdong Wang; Hillary A. Schuessler; Douglas D. Richardson; et al. (Pharmaceutical Research, 2023)

Flame retardant and multifunctional BC/MXene/MSiCnw/FRTPU aerogel composites with superior electromagnetic interference shielding via “Consolidating” method - Hengrui Wang; Kexin Chen; Yongqian Shi; Yanjun Zhu; Songqiong Jiang; Yan Liu; Shijie Wu; Chenxin Nie; Libi Fu; Yuezhan Feng; Pingan Song (Chemical Engineering Journal, 2023)

Study on detection method of microplastics in farmland soil based on hyperspectral imaging technology - Lijia Xu; Yanjun Chen; Ao Feng; Xiaoshi Shi; Yanqi Feng; Yuping Yang; Yuchao Wang; Zhijun Wu; Zhiyong Zou; Wei Ma; Yong He; Ning Yang; et al. (Environmental Research, 2023)

An integrated slot allocation model for time-space-dimensional noise reduction - Huilin Feng; Rong Hu; Junfeng Zhang; Yanjun Wang; Yutong Zhang (Transportation Research Part D: Transport and Environment, 2023)

ROS-activated selective fluorescence imaging of cancer cells via the typical LDH-based nanozyme - Zhengdi Wang; Jiancheng Liu; Min Feng; Kai Song; Kaitao Li; Wendi Liu; Shanyue Guan; Yanjun Lin (Chemical Engineering Journal, 2023)

The degradation of high emulsified oil wastewater in an intermittently-aerated MBBR packed with magnetic polystyrene particles - Ying Chen; Fengyuan Zhang; Feng Zhao; Xiaoshuang Shi; Yanjun Wu; Rongbo Guo; Quan Feng (Environmental Pollution, 2023)

Insights into the catalytic mechanism of a type I sulfide quinone oxidoreductase (SQR) from Acidithiobacillus caldus - Xiaoyang Lu; Linghui Zhao; Yanjun Tong; Hailin Yang; Shoushuai Feng (Systems Microbiology and Biomanufacturing, 2023)

Enhancement of acid tolerance of Escherichia coli by introduction of molecule chaperone CbpA from extremophile - Zhenming Jiang; Jie Lu; Yanjun Tong; Hailin Yang; Shoushuai Feng (World Journal of Microbiology and Biotechnology, 2023)

Seismicity induced by geological CO2 storage: A review - Yuxiang Cheng; Wenna Liu; Tianfu Xu; Yanjun Zhang; Xinwen Zhang; Yunyan Xing; Bo Feng; Yi Xia (Earth-Science Reviews, 2023)

Structural elucidation of a novel polysaccharide from Ophiopogonis Radix and its self-assembly mechanism in aqueous solution - Bei Wang; Bin Huang; Bing Yang; Liang Ye; Jingqi Zeng; Zhiwei Xiong; Yaping Chen; Shuchen Guo; Yanjun Yang; Weikun Ma; Maomao Zhu; Xiaobin Jia; et al. (Food Chemistry, 2023)

Application of Large-Scale Hydraulic Fracturing for Reducing Mining-Induced Stress and Microseismic Events: A Comprehensive Case Study - Hongpu Kang; Pengfei Jiang; Yanjun Feng; Fuqiang Gao; Zhen Zhang; Xiaogang Liu (Rock Mechanics and Rock Engineering, 2023)

Imidazolium-based ionic liquid confined into ordered mesoporous MCM-41 for efficient dehumidification - Lurong Ge; Yaohui Feng; Yanjun Dai; Ruzhu Wang; Tianshu Ge (Chemical Engineering Journal, 2023)

Urinary polycyclic aromatic hydrocarbon metabolites and depression: a cross-sectional study of the National Health and Nutrition Examination Survey 2005–2016 - Xiaobing Feng; Ruyi Liang; Da Shi; Dongming Wang; Yanjun Guo; Weihong Qiu; Man Cheng; Tao Xu; Chaoqian Dong; Min Zhou; Weihong Chen (Environmental Science and Pollution Research, 2022)

Identification and management of GCK-MODY complicating pregnancy in Chinese patients with gestational diabetes - Yanyan Jiang; Fusong Jiang; Ming Li; Qingkai Wu; Chenming Xu; Rong Zhang; Mingqiang Song; Yanzhong Wang; Ying Wang; Yating Chen; Juan Zhang; Xiaoxu Ge; et al. (Molecular and Cellular Biochemistry, 2022)

Projecting future changes in extreme climate for maize production in the North China Plain and the role of adjusting the sowing date - Dengpan Xiao; Huizi Bai; De Li Liu; Jianzhao Tang; Bin Wang; Yanjun Shen; Jiansheng Cao; Puyu Feng (Mitigation and Adaptation Strategies for Global Change, 2022)

Dysregulated lncRNA and mRNA may promote the progression of ischemic stroke via immune and inflammatory pathways: results from RNA sequencing and bioinformatics analysis - Yingshuang Wang; Feifei Feng; Pingping Zheng; Lijuan Wang; Yanjun Wang; Yaogai Lv; Li Shen; Kexin Li; Tianyu Feng; Yang Chen; Zhigang Liu; Yan Yao (Genes & Genomics, 2022)

Identification of MicroRNAs as potential biomarkers for detecting ischemic stroke - Kexin Li; Li Shen; Pingping Zheng; Yanjun Wang; Lijuan Wang; Xiaoli Meng; Yaogai Lv; Zhiqiang Xue; Xin Guo; Anning Zhang; Pan Pan; Chunli Bi; et al. (Genes & Genomics, 2022)

Characteristics and Causes of Extreme Rainfall Induced by Binary Tropical Cyclones over China - Mingyang Wang; Fumin Ren; Yanjun Xie; Guoping Li; Ming-Jen Yang; Tian Feng (Asia-Pacific Journal of Atmospheric Sciences, 2021)
Binary tropical cyclones (BTC) often bring disastrous rainfall to China. From the viewpoint of the extreme of the BTC maximum daily rainfall, the characteristics of BTC extreme rainfall (BTCER) during 1960–2018 are analyzed, using daily rainfall data; and some representative large-scale mean flows, in which the associated BTCs are embedded, are analyzed. Results show that the frequency of BTCER shows a decreasing trend [−0.49 (10 yr) −1 ] and is mainly distributed within the BTC heavy rainstorm interval (100 mm ≤ BTCER

Identification of Ala2Thr mutation in insulin gene from a Chinese MODY10 family - Juan Zhang; Yanjun Liu; Ming Li; Xiaoxu Ge; Ying Wang; Xin Huang; Di Yang; Rong Zhang; Yating Chen; Ming Lu; Jun Yin; Mingqiang Song; et al. (Molecular and Cellular Biochemistry, 2020)

An improved minimum bounding rectangle algorithm for regularized building boundary extraction from aerial LiDAR point clouds with partial occlusions - Maolin Feng; Tonggang Zhang; Shichao Li; Guoqing Jin; Yanjun Xia (International Journal of Remote Sensing, 2020)

Caspase-8 restricts natural killer cell accumulation during MCMV Infection - Yanjun Feng; Lisa P. Daley-Bauer; Linda Roback; Marc Potempa; Lewis L. Lanier; Edward S. Mocarski (Medical Microbiology and Immunology, 2019)

Caspase-8-dependent control of NK- and T cell responses during cytomegalovirus infection - Yanjun Feng; Lisa P. Daley-Bauer; Edward S. Mocarski (Medical Microbiology and Immunology, 2019)

Structural characterisation of a full-length mitochondrial outer membrane TOM40 preprotein translocase: implications for its interaction with presequence peptides - Wei Feng; Jinwen Li; Yanjun Liang; Yongqiang Zhang; Shu Jie Li (European Biophysics Journal, 2019)

Imidazole-Bearing Polymeric Micelles for Enhanced Cellular Uptake, Rapid Endosomal Escape, and On-demand Cargo Release - Di Lu; Yang An; Simin Feng; Xiaodan Li; Aiping Fan; Zheng Wang; Yanjun Zhao (AAPS PharmSciTech, 2018)

Arg913Gln of SLC12A3 gene promotes development and progression of end-stage renal disease in Chinese type 2 diabetes mellitus - Rong Zhang; Langen Zhuang; Ming Li; Juan zhang; Weijing Zhao; Xiaoxu Ge; Yating Chen; Feng Wang; Niansong Wang; Yuqian Bao; Limei Liu; Yanjun Liu; et al. (Molecular and Cellular Biochemistry, 2018)

Transcriptome analysis reveals that constant heat stress modifies the metabolism and structure of the porcine longissimus dorsi skeletal muscle - Yue Hao; Yuejin Feng; Peige Yang; Yanjun Cui; Jiru Liu; Chunhe Yang; Xianhong Gu (Molecular Genetics and Genomics, 2016)

The angiotensin-I converting enzyme gene I/D variation contributes to end-stage renal disease risk in Chinese patients with type 2 diabetes receiving hemodialysis - Ming Lu; Jianzhong Zhang; Ming Li; Xiaoxu Ge; Xu Dai; Jiao Zhao; Mingzhou Fu; Tao Wang; Xiyao Fang; Can Li; Rong Zhang; Weijing Zhao; et al. (Molecular and Cellular Biochemistry, 2016)

Physical statistical algorithm for precipitable water vapor inversion on land surface based on multi-source remotely sensed data - YongQian Wang; JianCheng Shi; Hao Wang; WenLan Feng; YanJun Wang (Science China Earth Sciences, 2015)

Isolation and functional characterization of seed-specific FAD2-1 promoter from cotton (Gossypium hirsutum L) - Feng Liu; YanPeng Zhao; Xiaodong Wang; Yanjun Li; Jie Sun (Journal of Plant Biochemistry and Biotechnology, 2015)

STAT4 genetic polymorphisms association with spontaneous clearance of hepatitis B virus infection - Yanjun Lu; Yaowu Zhu; Jing Peng; Xiong Wang; Feng Wang; Ziyong Sun (Immunologic Research, 2015)

Co-expression of Oct-4 and Nestin in human breast cancers - Caigang Liu; Xuezhao Cao; Yanjun Zhang; Hong Xu; Ruishan Zhang; Yunfei Wu; Ping Lu; Feng Jin (Molecular Biology Reports, 2012)

New eolian red clay sequence on the western Chinese Loess Plateau linked to onset of Asian desertification about 25 Ma ago - Xiaoke Qiang; Zhisheng An; Yougui Song; Hong Chang; Youbin Sun; Weiguo Liu; Hong Ao; Jibao Dong; Chaofeng Fu; Feng Wu; Fengyan Lu; Yanjun Cai; et al. (Science China Earth Sciences, 2011)